2012
DOI: 10.1166/jnn.2012.4262
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Cobalt Amorphous Alloys Under Field Annealing

Abstract: Crystallization of Co-rich amorphous ribbons annealed under a 10 Oe external magnetic field at the early 30 minutes from their glassy status to supercooled liquid status is investigated by high-resolution transmission microscope (HR-TEM), Selected Area Fourier Transform (SA-FT), X-ray diffraction (XRD) and differential scanning calorimetry (DSC). Results indicate that the short-rang ordering feature can be refined very well in specimen annealed under temperatures about 87.4 degrees C below their glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…3b-d). Different from the typical salt-pepper contrast nanostructure for the amorphous phase as observed in TEM images of the as-spun ribbons, 33 the annealed samples exhibit nanocrystalline features with distinct and unique characteristics that cannot be completely seen in their XRD patterns (Fig. 2) or SEM images (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…3b-d). Different from the typical salt-pepper contrast nanostructure for the amorphous phase as observed in TEM images of the as-spun ribbons, 33 the annealed samples exhibit nanocrystalline features with distinct and unique characteristics that cannot be completely seen in their XRD patterns (Fig. 2) or SEM images (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…In our previous article, the HR-TEM confirmed that the as-spun ribbons are indeed in amorphous phases, showing typical salt-pepper morphologies. 33 All the annealed ribbons exhibit cross-section morphologies distinguished from the as-spun ribbons due to the spots of corrosion of crystalline grains across the ribbons. The ribbons annealed without field show many precipitated particles dispersed across the ribbon (dark areas in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear overlap of the Co and O distributions, and subsequent image analysis indicates that the position of the N signal is highly correlated to that of the Co (Figure S5, Supporting Information). X-ray diffraction (XRD) (Figure 3e) showed several wide peaks, assigned to CoO (JCPDS 43-1004) and poorly crystallized Co metal, [52,53] superimposed on a broad background due to the ketjenblack. Figure 3f shows the results of X-ray photoelectron spectroscopy (XPS) measurements of Co 2p binding energy.…”
mentioning
confidence: 99%